The role of Women Regarding the Achievement of Sustainable Development Goal 13 in the Post-pandemic Era (Dissertare, 2022)
The participation of women in actions to achieve sustainable development is a topical issue of global priority and urgency that must be reviewed, considering the crucial role that women's contributions could play in achieving that goal. The objective of the work is to reflect on the role of women in the fulfillment of sustainable development goal 13 (SDG13 for its acronym in English), including their contribution in the proposal and execution of actions to avoid the factors that cause climate change (CC) in the post-pandemic era. The bibliographic review carried out allowed us to understand the limitations and discrimination that prevent women's participation in actions aimed at meeting the goals of SDG13, as well as in other objectives of the 2030 Agenda, obstacles that were even greater during the confinement resulting from the COVID-19 pandemic. The scientific works covered in this review, alluding to actions to avoid CC and its negative effects, show the need to implement these actions and warn about the greater consequences of not complying with them. It is necessary to reflect, not only on the fundamental role of women in the adoption of urgent measures to combat CC and its effects, but also on the importance of empowering women, from the position they occupy to allow their contribution can serve to address global challenges due to climate, from whose impact the female population does not escape.
Keywords: discrimination; gender equality; sustainable development; climate change